2017
DOI: 10.1016/j.compstruct.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

An integrated numerical model for investigating guided waves in impact-damaged composite laminates

Abstract: This paper presents a novel numerical technique that combines predictions of impact-induced damage and subsequent ultrasonic guided-wave propagation in composite laminates, with emphasis on the development and verification of the modelling framework. Delamination and matrix cracking are considered in the modelling technique, which is validated by experimental measurements on a carbon-fibre/epoxy plate using a drop-weight impact tower and a scanning laser vibrometer. Good agreement has been found between simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…With S 0 being three times faster than A 0 , one can easily choose the propagating distance to avoid any overlapping between the generated modes. Furthermore, the ratio of amplitudes between S 0 to A 0 is around 4%, which suggests neglecting the S 0 contribution, in accordance with the literature [25]. Therefore, the received mode will be almost a pure A 0 mode with negligible interference of the S 0 mode.…”
Section: Interaction Of a 0 Mode With Impact Damage And Comparison Be...supporting
confidence: 87%
See 2 more Smart Citations
“…With S 0 being three times faster than A 0 , one can easily choose the propagating distance to avoid any overlapping between the generated modes. Furthermore, the ratio of amplitudes between S 0 to A 0 is around 4%, which suggests neglecting the S 0 contribution, in accordance with the literature [25]. Therefore, the received mode will be almost a pure A 0 mode with negligible interference of the S 0 mode.…”
Section: Interaction Of a 0 Mode With Impact Damage And Comparison Be...supporting
confidence: 87%
“…The delamination reshapes the wavefield in the damaged and undamaged regions. In particular, it was found that the contribution of the delamination in the scattered wavefield is ~50% higher than the one corresponding to the matrix cracks [25].…”
Section: Influence Of the Damage Depth And Size On The Scattering Dir...mentioning
confidence: 94%
See 1 more Smart Citation
“…Previous investigators have reported the use of numerical simulations to study guided wave propagation and interaction with delaminations. [35][36][37][38][39][40][41][42][43][44] Guo and Cawley 35 used a two-dimensional (2D) finite element method (FEM) with plane strain assumption to study the reflection of the S0 mode from a delamination in unidirectional and cross-ply laminates. Ramadas et al 36,37 investigated the A0 mode interaction with the symmetric and asymmetric delaminations using a 2D model.…”
Section: Introductionmentioning
confidence: 99%
“…Leckey and Seebo 42 conducted a preliminary simulation to investigate differences in trapped energy for multilayer delaminations, and their studies showed that the trapped energy increases at the composite surface when additional delaminations exist through the composite thickness. In addition, 3D modeling of guided wave propagation and interaction with the actual impact damage was investigated in Leckey et al 43 and Zhang et al 44 These studies have facilitated our understanding of guided wave-based delamination detection using wavefield analysis. However, the numerical and experimental characterization of guided wave interactions with multilayer delaminations using wavenumber analysis and their sensitivity to the delamination severity are very limited.…”
Section: Introductionmentioning
confidence: 99%